Perception of the general population in Ciudad Valles, San Luis Potosi regarding waste production in hairdressing salons - Maldonado-Miranda, Juan José; Alonso-Castro, Ángel Josabad; Carranza-Álvarez, Candy (JNRD - Journal of Natural Resources and Development, 2016)
Hairdressing salons offer a wide range of services including treatments for hair and skin. However, these activities result in the production of residues that are improperly discharged into drainage, generating a negative impact on the environment. This study provides results of a first stage in a project regarding the analysis of waste disposal in hairdressing salons in the municipality of Ciudad Valles, San Luis Potosi, Mexico. Information gathering was conducted through a field work study by surveys given to workers in hairdressing salons in Ciudad Valles. The information presented in this study indicates that in hairdressing salons in Ciudad Valles there is no management plan for the management of waste that could be severely impacting the environment. The information presented here will be the basis for identifying priority areas for intervention, developing new research projects and setting new environmental policies. In addition, the results presented here can be extrapolated to many rural and urban areas all over Mexico.
Keywords: Waste; Hairdressing salons; Pollution; Legislation